Sure! Let's create a system of equations consisting of one linear equation and one quadratic equation.
System of Equations:
- Linear Equation: \( y = 2x + 3 \)
- Quadratic Equation: \( y = x^2 - 4 \)
Step 1: Determine a solution
To determine whether a given point is a solution to the system of equations, we can substitute the \( x \) and \( y \) coordinates of that point into both equations.
Let’s say we want to check if the point \( (1, 5) \) is a solution.
Substitute into the linear equation:
- Substitute \( x = 1 \) into the linear equation: \[ y = 2(1) + 3 \] \[ y = 2 + 3 = 5 \] The calculated \( y \) value is \( 5 \), which matches with the \( y \) value of the point \( (1, 5) \).
Substitute into the quadratic equation:
- Substitute \( x = 1 \) into the quadratic equation: \[ y = (1)^2 - 4 \] \[ y = 1 - 4 = -3 \] The calculated \( y \) value is \( -3 \), which does not match with the \( y \) value of the point \( (1, 5) \).
Conclusion:
Since the point \( (1, 5) \) satisfies the linear equation but not the quadratic equation, it is not a solution for the system of equations.
Step 2: Finding a solution point
Let's find a solution point by equating the two equations: \[ 2x + 3 = x^2 - 4 \] Rearranging gives: \[ x^2 - 2x - 7 = 0 \] We can solve this quadratic equation using the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] Where \( a = 1, b = -2, c = -7 \): \[ x = \frac{2 \pm \sqrt{(-2)^2 - 4(1)(-7)}}{2(1)} \] \[ x = \frac{2 \pm \sqrt{4 + 28}}{2} \] \[ x = \frac{2 \pm \sqrt{32}}{2} \] \[ x = \frac{2 \pm 4\sqrt{2}}{2} \] \[ x = 1 \pm 2\sqrt{2} \]
This gives us two possible \( x \) values:
- \( x_1 = 1 + 2\sqrt{2} \)
- \( x_2 = 1 - 2\sqrt{2} \)
Next, let's find the corresponding \( y \) values. Using the linear equation:
- For \( x_1 = 1 + 2\sqrt{2} \): \[ y_1 = 2(1 + 2\sqrt{2}) + 3 = 2 + 4\sqrt{2} + 3 = 5 + 4\sqrt{2} \]
- For \( x_2 = 1 - 2\sqrt{2} \): \[ y_2 = 2(1 - 2\sqrt{2}) + 3 = 2 - 4\sqrt{2} + 3 = 5 - 4\sqrt{2} \]
Final Solutions:
The system has two solutions:
- \( \left( 1 + 2\sqrt{2}, 5 + 4\sqrt{2} \right) \)
- \( \left( 1 - 2\sqrt{2}, 5 - 4\sqrt{2} \right) \)
Step 3: Graphing the Solution Set
To graph the system of equations:
-
Linear Equation:
- The equation \( y = 2x + 3 \) is a straight line.
-
Quadratic Equation:
- The equation \( y = x^2 - 4 \) is a parabola opening upwards.
Intersection Points
Plotting these equations on a coordinate plane reveals their intersection points, which correspond to the solutions we derived.
- Label the points of intersection as \( A \left( 1 + 2\sqrt{2}, 5 + 4\sqrt{2} \right) \) and \( B \left( 1 - 2\sqrt{2}, 5 - 4\sqrt{2} \right) \).
Graphing Instructions:
- Draw the linear line according to the slope-intercept form \( y = 2x + 3 \).
- Draw the parabola for \( y = x^2 - 4 \) (it intersects the y-axis at -4).
- Locate the intersection points computed earlier and label them \( A \) and \( B \).
Example Graph Illustration:
It's generally not possible to provide an actual graphical representation here, but you can sketch the graph on paper or use graphing software to visualize this.
Conclusion
This gives us a complete view of how to create a system of equations with one linear and one quadratic equation, how to check if points are solutions, and how to identify and graph solutions.